Molecular mechanisms of pruritus in prurigo nodularis - Shao, Yixin; Wang, Duoqin; Zhu, Yiqi; Xiao, Zijing; Jin, Taiyu; Peng, Lisi; Shen, Yanyun; Tang, Hui (Frontiers in Immunology, 2023)
Pruritus is the most common symptom of dermatological disorders, and prurigo nodularis (PN) is notorious for intractable and severe itching. Conventional treatments often yield disappointing outcomes, significantly affecting patients' quality of life and psychological well-being. The pathogenesis of PN is associated with a self-sustained "itch-scratch" vicious cycle. Recent investigations of PN-related itch have partially revealed the intricate interactions within the cutaneous neuroimmune network; however, the underlying mechanism remains undetermined. Itch mediators play a key role in pruritus amplification in PN and understanding their action mechanism will undoubtedly lead to the development of novel targeted antipruritic agents. In this review, we describe a series of pruritogens and receptors involved in mediating itching in PN, including cytokines, neuropeptides, extracellular matrix proteins, vasculogenic substances, ion channels, and intracellular signaling pathways. Moreover, we provide a prospective outlook on potential therapies based on existing findings.